The Effectiveness Of Ted Short Video In Improving EYL Speaking Skills - Suwandhi, Aldi Adam; Rachmaawati, Etika (Journal of English Education Program (JEEP), 2024)
The study concerned with the effectiveness of TED short video in improving EYL speaking skills. The purposes were to find out whether the use of TED short videos improved students’ speaking skills for learning purposes and to figure out whether the use of TED videos could eliminate students’ fears when speaking in class. A mixed-method study was used as a research design that combined a pre-experimental design and a descriptive study. This study involved the seventh-grade students of a Junior High School in Ciamis in the academic year 2023/2024. Two instruments in the form of the speaking test and the questionnaires were administered to the students. An inferential analysis was used to analyze the speaking test while an exploratory data analysis was used to analyze the questionnaires. The findings indicated that the application of TED short video helps enhancing EYL speaking skills in the seventh grade of a Junior High School in Ciamis. In other words, it could improve students’ speaking skills for learning purposes. The findings also indicated that the use of TED short videos could eliminate students’ fears when speaking in class because it was easy, fun, enjoyable, and good for learning to speak. Other reasons, it could also increase their confidence to use English after participating in speaking class. Therefore, the teachers are suggested to get alternative teaching media in teaching speaking by using TED short videos. Besides that, it is recommended that students use TED short videos to improve their speaking performance. It is suggested for other researchers to get some advantages of this study because it can be used as a reference source for the same topic.